Proceedings of the Ocean Drilling Program 1993
DOI: 10.2973/odp.proc.sr.130.050.1993
|View full text |Cite
|
Sign up to set email alerts
|

Hiatus and Tephrochronology of the Ontong Java Plateau: Correlation with Regional Tectono-Volcanic Events

Abstract: Evidence of regional tectonism/volcanism in the southwestern Pacific is inferred from the presence of hiatuses and/or ash encountered in the sections drilled on the Ontong Java Plateau at Ocean Drilling Program Sites 803-807 and Deep Sea Drilling Project Sites 288 and 289/586. In general, hiatuses on the plateau do not correlate well with one another or with the deep-sea hiatuses reported by others. Correspondence between groups or clusters of ash horizons between sites on the plateau is better in the upper pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The relative abundance of terrigenous material at 803 and 805 is 4-5%, on average, and this material is predominantly comprised of smectite, with significantly lesser amounts of plagioclase ($5-10· less) and quartz (>10· less) (Krissek and Janecek, 1993). Small ash layers have been identified at 807A and 807C (Kroenke et al, 1993). The ash layers are generally between <1 and 7 cm in thickness, though a few ash layers as thick as 10 (1349.70 mbsf), 15 (1349.95 mbsf), and 33 (1173.64 mbsf) cm are identified.…”
Section: Sample Location and Descriptionmentioning
confidence: 97%
See 1 more Smart Citation
“…The relative abundance of terrigenous material at 803 and 805 is 4-5%, on average, and this material is predominantly comprised of smectite, with significantly lesser amounts of plagioclase ($5-10· less) and quartz (>10· less) (Krissek and Janecek, 1993). Small ash layers have been identified at 807A and 807C (Kroenke et al, 1993). The ash layers are generally between <1 and 7 cm in thickness, though a few ash layers as thick as 10 (1349.70 mbsf), 15 (1349.95 mbsf), and 33 (1173.64 mbsf) cm are identified.…”
Section: Sample Location and Descriptionmentioning
confidence: 97%
“…There are few well-defined ash layers in the upper 800 m of the section. Of those, 50% have trace or 1% glass while the other 50% average $12% glass (Kroenke et al, 1993).…”
Section: Sample Location and Descriptionmentioning
confidence: 99%
“…Middle Eocene foredeep sediments and olistostromes record the collision of the Norfolk-New Caledonia Ridge continental ribbon with the forearc region of the intra-oceanic Loyalty-dEntrecasteaux arc [Aitchison et al, 1995]. In addition, Kroenke et al [1993] suggested that the age of hiatuses described for rock samples from DSDP Site 289 and ODP Site 803 (both on the Ontong Java Plateau) are close to 43 Ma, indicating a tectonic event in the Southwest Pacific. The tectonic event that occurred at 43 Ma also influenced the northern Australian margin.…”
Section: Mamentioning
confidence: 98%
“…A second, but not so well-documented, group of events represented by hiatuses or times of reduced sedimentation are recognized in the pelagic cover of Cretaceous Pacific seamounts (Sliter, 1992;Kroenke et al, 1993;Sliter and Leckie, 1993). The meager record of Cretaceous pelagic sedimentation from Allison Guyot shows only broad hiatuses in the Cenomanian to Maastrichtian sequence (Fig.…”
Section: Younger Cretaceous Eventsmentioning
confidence: 99%